The impact of co-production : from community engagement to social justice - Ersoy, Aksel (Connected communities (Bristol, England), 2017)
This text brings together academics, artists, practitioners and 'community activists' to explore the possibilities for and tensions of social justice work under the contemporary drive for community-oriented 'impact' in the academy.